Preservation of chocolate muffins with Lemon Balm, Oregano, and Rosemary extracts - Pedrosa, Mariana C. (2018)
Muffins are snacks made from flour and chocolate and preserved with synthetic additives. Following consumer trends, the search for natural food additives has gained traction. Plants such as rosemary, lemon balm, and oregano were analyzed following an optimization of ultrasound assisted extraction, screened for their antioxidant and antimicrobial activity and incorporated in chocolate muffins, comparing them to synthetic preservatives over the course of 8 days. The nutritional profile, organic and fatty acids, soluble sugars, texture profile, external color and digital imaging of the muffin pores were analyzed. Slight changes were sought for the muffins incorporated with the natural extracts. By means of linear discriminant analysis, rosemary extract was considered the most promising extract to preserve the muffins due to its similarity to potassium sorbate, showing no changes in the muffins it was incorporated in, although it showed a lower amount of phenolic compounds when compared to lemon balm.